A Monitoring System of Soil Moisture for Fertigation System using IOT Application - Md Zailani, Muhammad Zulhilmi; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2021)
The advancement of agricultural technologies is gaining momentum, with the majority of these advancements assisting farmers in the facilitation of their plantation. Smart devices and the Internet of Things (IoT) are being used to help reduce the cost and time spent on labor. In order to meet the demands of the population, it is also necessary to improve the quality and quantity of agricultural production. The Internet of Things has been instrumental in monitoring the condition of a plantation in Malaysia, where the climate is unpredictable and it is impossible to predict when the rain will fall. As a result, a monitoring system based on Internet of Things application for agriculture was developed to assist farmers. This system enables farmers to monitor soil moisture levels that could otherwise result in undesirable consequences. It is possible for this system, which uses the Blynk application installed on smartphones, to check the soil condition at the plantation in order to determine whether the soil is dry or saturated with water. The prototype has been tested in both indoor and outdoor conditions at different times. The results of the experiment are obtained, and the goal is achieved. The user can monitor the condition of the soil over time using the Blynk application. There is a difference between indoor and outdoor plants because outdoor plants receive more sunlight and are exposed to it more directly than indoor plants but the results are not significantly different.